2022
DOI: 10.3390/vetsci9060277
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Tumor Grade and Proliferation Indices before and after Short-Course Anti-Inflammatory Prednisone Therapy in Canine Cutaneous Mast Cell Tumors: A Pilot Study

Abstract: Glucocorticoid administration is a common clinical practice that attempts to decrease the inflammation associated with and improve the resectability of canine mast cell tumors (MCTs). However, the impact of neoadjuvant glucocorticoids on the histological features and proliferation indices of canine MCTs is unknown. The objective of this study was to evaluate changes in tumor grade, mitotic count, Ki67, AgNOR, and AgNORxKi67 scores following short-course anti-inflammatory neoadjuvant prednisone in canine patien… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 96 publications
0
1
0
1
Order By: Relevance
“…Additionally, the effect of neoadjuvant VBL‐P on MC and proliferation indices remains unclear. Whereas previous evidence in dogs suggest that neoadjuvant prednisolone does not affect most histological features, 21,41,59 several studies in humans highlight the effect of cytotoxic chemotherapy on MC and proliferation indices. Whereas in vitro studies suggest that microtubules‐disruptive agents such as vinblastine and taxol can artificially increase the MC via cell cycle arrest, 60,61 clinical studies showed that taxanes‐based‐NAC protocols can decrease MC 61–64 .…”
Section: Discussionmentioning
confidence: 92%
“…Additionally, the effect of neoadjuvant VBL‐P on MC and proliferation indices remains unclear. Whereas previous evidence in dogs suggest that neoadjuvant prednisolone does not affect most histological features, 21,41,59 several studies in humans highlight the effect of cytotoxic chemotherapy on MC and proliferation indices. Whereas in vitro studies suggest that microtubules‐disruptive agents such as vinblastine and taxol can artificially increase the MC via cell cycle arrest, 60,61 clinical studies showed that taxanes‐based‐NAC protocols can decrease MC 61–64 .…”
Section: Discussionmentioning
confidence: 92%
“…2.1. pp. 6 -21. mayo -junio 2023 www.alfapublicaciones.com fármacos en la clínica está destinado a disminuir la inflamación y mejorar la resecabilidad del MCT (Klahn et al, 2022).…”
Section: Discussionunclassified